Ecological index of gastropods in the Tananan River, Mamasa Regency - Andi Nur Samsi; Irnayanti Bahar (Jurnal Penelitian Pendidikan IPA, 2026)
Research on gastropod ecological indices is important for determining ecosystem stability. Previous research only focused on the abundance of gastropods. The purpose of this study was to analyze the diversity index (H'), evenness index (J'), and dominance index (C) of gastropods in the Tananan River, the research location. The method used included transect and plot sampling at two observation stations, with random sampling. Station A had a sandy substrate, and Station B had a rocky substrate, close to residential areas. Species identification was carried out morphologically, and the data were analyzed using the Shannon-Wiener, Pielou, and Simpson ecological indices. The results showed that gastropod diversity was in the moderate category (H’ = 1,785 – 2,265), evenness values (J’ = 0,893 – 0,975) indicated an even distribution of species, and no specific species were dominant (C = 0,213 – 0,318). These findings indicate a moderate ecosystem condition. Local communities utilize gastropods, particularly Pila ampulacea and Pomacea canaliculata, as side dishes. The processing is still simple and adds to the uniqueness of local cuisine. In conclusion, gastropod ecological indices can be effective biological indicators of ecosystem health. The use of gastropods for public consumption requires further research due to the discovery of Indoplanorbis exustus in the river.